Clinical researchTumour necrosis factor gene polymorphisms and migraine in Greek children - Pappa, Styliani; Hatzistilianou, Maria; Kouvatsi, Anastasia; Pantzartzi, Chrysa; Sakellaropoulou, Afroditi; Pavlou, Evangelos; Mavromichales, Ioannis; Athanassiadou, Fanni (Archives of Medical Science, 2010)
Introduction: Migraine is considered to be a multifactorial, complex disease. Various genetic and environmental factors contribute to the manifestation of this disease. The aim of this study was to determine whether polymorphisms in the tumour necrosis factor (TNF) region are associated with the risk of migraine. We examined the association between 6 single nucleotide polymorphisms in the coding regions of TNF- and TNF-β genes and migraine. Material and methods: The study included two groups of children (group A and group B). Group A consisted of 103 unrelated children with typical migraine without aura 5-14 years of age. Group B (control group) consisted of 178 unrelated healthy children. The diagnosis of migraine was, in all patients, made according to the International Classification of Headache Disorders (ICHD II). Results: According to our results positive family history was present in 62.2% of patients of group A. No significant differences were found in the frequencies of genotypes or alleles between patients and controls. The non-parametric analyses of variance showed no significant differences in the age at onset between genotype groups of the TNF- and TNF-β gene polymorphisms. Comparison of genotype frequencies between boys and girls in affected patients and control individuals were not significantly different (p = 0.089, p =0.073 respectively). The distribution of TNF polymorphisms was not associated with the presence of family history of migraine in patients. Conclusions: Our data indicate that TNF- and TNF-β gene polymorphisms are not a significant risk factor for migraine without aura in Greek children.